2006
DOI: 10.1002/hup.777
|View full text |Cite
|
Sign up to set email alerts
|

The effects of concurrent cannabis use among ecstasy users: neuroprotective or neurotoxic?

Abstract: Edge Hill College of Higher EducationRunning head: concurrent cannabis use among ecstasy users. The research evidence regarding the potential effects of ecstasy suggests that it may be neurotoxic and that its use is associated with cognitive impairment. In recent years evidence has emerged suggesting that cannabinoids, the active ingredients in cannabis, can be neuroprotective under certain conditions. Given that many ecstasy users also consume cannabis at the same time, the possibility emerges that these indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…In fact, many studies showing significant impairment in ecstasy users measured more complex forms of working memory function, especially in tasks tapping updating functions (e.g. Fisk et al, 2006;Wareing et al, 2004Wareing et al, , 2007. In line with this argument, we found that, as in the executive functioning assessments, ecstasy use was associated with increased errorproneness in the SWM task, independent of sex and IQ effects.…”
Section: Working Memorysupporting
confidence: 77%
“…In fact, many studies showing significant impairment in ecstasy users measured more complex forms of working memory function, especially in tasks tapping updating functions (e.g. Fisk et al, 2006;Wareing et al, 2004Wareing et al, , 2007. In line with this argument, we found that, as in the executive functioning assessments, ecstasy use was associated with increased errorproneness in the SWM task, independent of sex and IQ effects.…”
Section: Working Memorysupporting
confidence: 77%
“…Thus, the findings of the current study are not consistent with the premise that cannabis, when used concomitantly with ecstasy protects against the neurotoxic effects of ecstasy on the serotonin axons, at least of sufficient magnitude to be identified within the current method. Independent studies have similarly failed to identify neuroprotective effects of concomitant cannabis use on behavioural measures in humans [37] .…”
Section: The Tilt Aftereffect As a Function Of Cannabis Usementioning
confidence: 99%
“…The lack of relationship between awareness of ecstasy's effects and the total of adverse effects reported does not support the assertion that users' reports of such effects may be magnified in any substantial way by media and other influences [6]. The concurrent use of alcohol, rather than cannabis, with ecstasy may be an important area for future research [4].…”
Section: Discussionmentioning
confidence: 86%
“…However, such findings are potentially subject to distorting influences such as the effects of other drugs used concurrently with ecstasy [4], sleep disturbance [5], and external influences such as media reports of ecstasy related harm which may increase users' propensity to attribute adverse effects to their use of the drug [6]. Statistical analysis of self-reported adverse effects can also be difficult due to distribution problems arising from a large number of zero scores for particular effects [3].…”
Section: Introductionmentioning
confidence: 99%